Carbon soot over layered sulfur impregnated coconut husk derived carbon: An efficient polysulfide suppressor for lithium sulfur battery. (March 2020) - Bharti, Vikram; Gangadharan, Ananya; Rao, Tata N.; Sharma, Chandra S.
Graphical abstract: Abstract: The present work introduces a facile strategy to develop an eco-friendly and inexpensive cathode material to accomplish the suppressing of polysulfide shuttle mechanism in lithium sulfur battery. The cathode design involves coconut husk derived carbon (CH) to host the insulating sulfur followed by a candle soot carbon over layer to barricade the lithium polysulfide dissolution to the electrolyte. The physical and electrochemical characterization clearly demonstrate the capability of CH to uphold the sulfur, therefore the cell could retain its reversible storage capacity without deteriorating the electrical contact with sulfur while cycling the cell. Further modification on sulfur impregnated carbon (SCH) by introducing a candle soot overlayer play the role of an ideal interlayer by assuring fast lithium ion diffusion and polysulfide blocking. Thus candle soot carbon coated SCH demonstrated an outstanding electrochemical performance and exhibited the capacity of 1347 mA h.g −1 at 100 mA.g −1 and retained the capacity of ∼400 mA h.g −1 even at a current density of as high as 5000 mA.g -1 .